Kalimat Baku Dalam Teks Laporan Hasil Observasi Kelas X SMA Negeri 1 Pagaran Tapah Darussalam Kabupaten Rokan Hulu, Riau - Faradina Widia Sari (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
There are five objectives of this research. First, describe standard sentences in terms of clarity of sentence structure. Second, describe standard sentences in terms of logical meaning. Third, describe standard sentences in terms of word savings. Fourth, describe standard sentences in terms of standard. Fifth, describe standard sentences in terms of spelling accuracy. This type of research is a qualitative research with descriptive method. The research instrument is the researcher himself. The background of this research is the students of class X SMA Negeri 1 Pagaran Tapah Darussalam Rokan Hulu Regency, Riau. The research entry is in the form of a report text on the observations of class X students of SMA Negeri 1 Pagaran Tapah Darussalam, Rokan Hulu Regency, Riau which was obtained from research data sources. There are five indicators reviewed at SMA Negeri 1 Pagaran Tapah Darussalam, namely clarity of sentence structure, logical meaning, word efficiency, word standardization, and spelling accuracy. Attendance in key research instrument (human instrument). The source of the research data was obtained by giving the report text assignments on the results of the observations to the students of SMA Negeri 1 Pagaran Tapah Darussalam. The data collection technique used is the study of documentation. The data validation technique used is the triangulation technique. There are five results of this study. First, the standard sentence form in terms of structural clarity, namely SMA Negeri 1 Pagaran Tapah Darussalam has 2 canteens. Second, the form of the sentence in terms of logical meaning, namely the prayer room is one of the places available in schools for prayer. Third, the form of the sentence in terms of word savings, namely Mading is an abbreviation of Wall Magazine. Fourth, the form of sentences in terms of standard words, namely SMAN 1 Pagaran Tapah Darussalam is a place for students to study. Fifth, sentence form in terms of spelling accuracy, namely the first canteen is located next to class XI IPA, while the second is located next to the new class.Based on the results of this study, it can be concluded that standard sentences and non-standard sentences were found in the report text of the observations of class X students of SMA Negeri 1 Pagaran Tapah Darussalam, Rokan Hulu Regency, Riau. The form of standard sentences and non-standard sentences is measured based on five predetermined indicators, namely structural clarity, logical meaning, word efficiency, word standardization, and spelling accuracy.